ANALISA DAMPAK BIAYA PRODUKSI TERHADAP KONSTRUKSI DAN MATERIAL PADA DESAIN BANGKU TAMAN UNTUK ANAK DI KOTA SURABAYA SEBAGAI UNSUR PENUNJANG ESTETIKA - Angga Wishnuprasetya (Fakultas Ekonomi Universitas 45 Surabaya, 2015)
Material of cement cast with fixed construction in nature and have the very massive forms and give the visual impression is very heavy and even in overall it isn’t provide the suitable characteristics to consume by children that are being seemed in the city park area is the specification contained on park benches especially for children in the city of Surabaya. Not infrequently, a bench that was intended for the children is actually widely used by adults. Consequently, many benches that can be said to be out of goals and objectives of the initial creation. In this study, the method that used are field observations that are supported by some of data to be analyzed to assess and provide some of exposure in terms of construction aspects that elaborated descriptively. It was followed by the method of aesthetic approach that is a special approach that emphasizes the aspects of art and design in relation to the appeals of aesthetic aspect by providing the conclusion that can be used as a reference in the process of creating park bench especially for children in the future, and it is expected able to provide answers to the simplicity of shape and the weakness of material that contained in the creating process of park bench especially for children effectively and efficiently that give impacts on production costs.